Corrigendum to “Preclinical evaluation of the safety and effectiveness of a new bioartificial cornea” [Bioact. Mater. 2023 (8) 29 265–278] - Yansha Hao; Jingting Zhou; Ju Tan; Feng Xiang; Zhongliang Qin; Jun Yao; Gang Li; Mingcan Yang; Lingqin Zeng; Wen Zeng; Chuhong Zhu (Bioactive Materials)
Cross-linking agents are frequently used to restore corneal properties after decellularization, and it is especially important to select an appropriate method to avoid excessive cross-linking. In addition, how to promote wound healing and how to improve scar formation require further investigation. To ensure the safety and efficacy of animal-derived products, we designed bioartificial corneas (BACs) according to the criteria for Class III medical devices. Our BACs do not require cross-linking agents and increase mechanical strength via self-cross-linking of aldehyde-modified hyaluronic acid (AHA) and carboxymethyl chitosan (CMC) on the surface of decellularized porcine corneas (DPCs). The results showed that the BACs had good biocompatibility and transparency, and the modification enhanced their antibacterial and anti-inflammatory properties in vitro. Preclinical animal studies showed that the BACs can rapidly regenerate the epithelium and restore vision within a month. After 3 months, the BACs were gradually filled with epithelial, stromal, and neuronal cells, and after 6 months, their transparency and histology were almost normal. In addition, side effects such as corneal neovascularization, conjunctival hyperemia, and ciliary body hyperemia rarely occur in vivo. Therefore, these BACs show promise for clinical application for the treatment of infectious corneal ulcers and as a temporary covering for corneal perforations to achieve the more time.